2015
DOI: 10.1074/jbc.m115.665331
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 3A Enzymes Catalyze the O6-Demethylation of Thebaine, a Key Step in Endogenous Mammalian Morphine Biosynthesis

Abstract: Background: Mammals synthesize endogenous morphine; the enzyme catalyzing thebaine O 6 -demethylation, a key late step, is uncharacterized. Results: Human cytochromes P450 (P450) 3A4 and 3A5 catalyzed thebaine O 6 -demethylation; the P450 3A-selective drug ketoconazole inhibited the reaction in human liver microsomes and rat brain homogenates. Conclusion: P450s 3A4 and 3A5 catalyze thebaine O 6 -demethylation in humans. Significance: Enzymes catalyzing all oxidations in the latter steps of mammalian morphine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Cytochrome P450 and germin-like protein (GLPs) were the most downregulated gene families representing with 5 and 7 members, respectively. Cytochrome P450s are the class of heme binding oxidase involved in a wide range of metabolic reactions of cell leading to synthesis of fatty acid, hormone, secondary metabolites and defense compounds 32 33 34 . Numerous reports exposed the important role of GLPs in maintaining the basal immunity by affecting the defense process in plants 35 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Cytochrome P450 and germin-like protein (GLPs) were the most downregulated gene families representing with 5 and 7 members, respectively. Cytochrome P450s are the class of heme binding oxidase involved in a wide range of metabolic reactions of cell leading to synthesis of fatty acid, hormone, secondary metabolites and defense compounds 32 33 34 . Numerous reports exposed the important role of GLPs in maintaining the basal immunity by affecting the defense process in plants 35 36 .…”
Section: Resultsmentioning
confidence: 99%
“…64 Subsequent studies showed that human P450s 3A4 and 3A5 can catalyze the O 6 -demethylation of thebaine (derived from salutaridine) and that P450 2D6 catalyzes the O 3 -demethylation of codeine, and thus all of the steps in morphine biosynthesis are now established in humans. 67 However, the extent of contribution of this pathway to endogenous control of pain remains to be determined.…”
Section: C-c Bond Forming Reactionsmentioning
confidence: 99%
“…In some cases, the same reaction can be catalyzed by an Fe/ α -KG dioxygenase in one species and by a P450 in another (e.g. thebaine O 6 -demethylation by an Fe/ α -KG dioxygenase in plants 465 and by P450s in mammals 67 ).…”
Section: C-c Bond Breaking Reactionsmentioning
confidence: 99%
“…The choice of a human oxidase and reductase was derived from the increasing knowledge that mammalian cells are able to synthesize morphine. The biosynthetic pathway delineated so far ( [24 ] and literature cited therein) includes similar metabolites and enzymes as in P. somniferum. After production of salutaridine in yeast the next challenge was the formation of morphine.…”
Section: Biosynthetic Steps: Enzymes and Genesmentioning
confidence: 99%